Een duivels dilemma: Abortus of tienermoeder? - Cense, Marianne (Religie & Samenleving, 2016)
Teenage pregnancy is controversial. Often the social environment of teenagers has a strong judgement on what they should do: abortion or parenthood. Although women in the Netherlands have legal and safe access to abortion, there is also a deep ambivalence about the morality of abortion manifest in politics and media. In this article I analyse the decision-making of girls who are confronted with an unintended pregnancy. In-depth interviews with 46 girls who got pregnant before their 20th birthday illuminate their motives for the choice they made. It also shows their resilience. Often, becoming pregnant and motherhood helped them to take better care of themselves. In that sense, pregnancy was a blessing in disguise, marking a turning point in a girl’s life. This was applicable to young mothers, but also to girls who had an abortion against the wishes of their social environment, since they took back control on their lives.